Pediatric Anesthesiology Practice Evolution in Benin, from the Study Research Realized in 2010 and 2020 - Akodjenou, Joseph; AHOUNOU, Ernest; ZOUMENOU, EUGÈNE (My University, 2023)
Introduction: This is a literature review on pediatric anesthesiology practice from 2010 to 2020 in two reference teaching hospitals of Cotonou: National University Hospital Centre (CNHU), and Lagoon--Mother and Child Hospital Centre (CHUMEL). Objective: To highlight the advances in pediatric anesthesia in Benin through the work carried out in 2010 and those of 2020 in the two reference hospitals in southern Benin. Patients and Methods: Data concerning the sociodemographic profile of patients, epidemiologic profile, human resources, infrastructures, equipment, medications and caregiving are examined. In this study, the work carried out in 2010 was compared to those in 2020. Results: The study carried out in 2010 included 512 children under 15 years, for a year’s duration; when in 2020, 345 children were included, all of which had surgery in a five months period. Equipment and Human ressources had improved with the creation of a pediatric critical care unit. The new monitoring material, anesthetic medications, and regional anesthesia technics were not practiced in 2010. Conclusion: This work shows that the practice of pediatric anesthesia in 2020 in the two reference hospitals in Benin, compared to previous years, is becoming increasingly satisfactory, even if anesthesia safety is not yet optimal.
Keywords: Pediatric Anesthesiology; Evolution; CHU-MEL